Application of the PIECES Framework Method in E-Report Evaluation - Muhammad Sholikin; Eko Sediyono; Hendry Hendry (Postgraduate, University of Mataram, 2023)
The evaluation of the E-report application at SMK N 1 Banyudono is integral for assessing its alignment with the latest curriculum guidelines and its effectiveness in meeting students' learning and assessment needs. This evaluation ensures that learning support technologies, such as E-report, stay relevant, responsive to user needs, and supportive of the school's long-term educational objectives. Using the PIECES method, the assessment of user satisfaction comprehensively considers Performance, Information, Economy, Control, Efficiency, and Services indicators. The Likert scale aids in gauging user satisfaction across various aspects. Quantitative data analysis involves 26 respondents, including teachers, homeroom teachers, curriculum staff, and school principals, providing a holistic perspective on learning and assessments management. The PIECES method and Likert scale evaluation reveal a satisfaction level of 4.52, categorizing it as